Using Paleoecological Methods to Study Long-Term Disturbance Patterns in High-Elevation Whitebark Pine Ecosystems - Jordin Hartley; Jennifer Watt; Andrea Brunelle (Fire)
Pinus albicaulis (whitebark pine) is a keystone species, providing food and habitat to wildlife, in high-elevation ecological communities. In recent years, this important species has been negatively impacted by changes in fire regimes, increased Dendroctonus ponderosae (mountain pine beetle) outbreaks associated with human landscape and climate modification, and the continued impact of the non-native Cronartium ribicola (white pine blister rust). This research investigates changes in fire occurrence, the establishment of Pinus albicaulis, and fuel availability at a high-elevation site in the Sawtooth National Recreation Area, Idaho, USA. Charcoal and pollen analyses were used to reconstruct fire and vegetation patterns for Phyllis Lake, Idaho, USA, over the past ~8200 cal y BP. We found that significant fire episodes occurred when the pollen accumulation rates (PARs) indicated more arboreal fuel availability, and we identified that Pinus albicaulis became well established at the site ~7200 cal y BP. The high-elevation nature of Phyllis Lake (2800 m) makes this record unique, as there are not many paleorecords at this high elevation from the Northern Rocky Mountains, USA. Additional high-elevation sites in Pinus albicaulis habitats will provide critical insight into the long-term dynamics of this threatened species.